Analisis Hasil Belajar Siswa pada Pembelajaran Pancasila Menggunakan Game E-Learning "PANCASILAKU" Berbasis SAC Kelas IV - Fa'iqotul Alfiyah; Frans Aditia Wiguna; Andri Pitoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze students' learning outcomes in Pancasila learning using the "PANCASILAKU" E-Learning Game based on Smart Apps Creator (SAC). The study was motivated by the low learning outcomes of students and the limited use of interactive learning media in Pancasila learning. This research employed a descriptive quantitative approach. The subjects consisted of 28 fourth-grade students of SDN Burengan 1, involving a limited trial of 8 students and a large-scale trial of 20 students. Data were collected through post-test assessments administered after students participated in learning activities using the "PANCASILAKU" E-Learning Game. The data were analyzed using descriptive quantitative techniques by calculating the percentage of students' learning mastery and learning outcomes. The results showed that classical learning mastery in the limited trial reached 100%, while the large-scale trial reached 90%. Furthermore, the post-test results obtained percentages of 92.5% in the limited trial and 88% in the large-scale trial, with an average score of 90.25%. These findings indicate that students achieved satisfactory learning outcomes after participating in Pancasila learning using the "PANCASILAKU" E-Learning Game based on Smart Apps Creator (SAC). Therefore, the media can support students in understanding the material on the implementation of Pancasila values in elementary schools.